1H-NMR based metabolomics study for the detection of the human urine metabolic profile effects of Origanum dictamnus tea ingestion. Issue 9 (6th September 2016) - Takis, Panteleimon G.; Oraiopoulou, Mariam-Eleni; Konidaris, Constantinos; Troganis, Anastassios N.
Abstract : NMR based metabolomics clarify the Origanum dictamnus tea effect upon the human urine metabolome. Abstract : 1 H NMR spectroscopy was employed to investigate the repercussion of Origanum dictamnus tea ingestion in several volunteers' urine metabolic profiles, among them two with chronic inflammatory bowel diseases (IBD), mild IBD and Crohn's disease. Herein, we demonstrate that the concentrations of a lot of urinary metabolites such as hippurate, trimethylamine oxide (TMAO), citrate, and creatinine are altered, which prompts the intestinal microflora function/content perturbation as well as kidney function regulation by dictamnus tea. Interestingly, our preliminary results showed that a high dose of dictamnus tea intake appeared to be toxic for a person with Crohn's disease, since it caused high endogenous ethanol excretion in urine. All subjects' metabolic effects caused by the dictamnus tea appeared to be reversible, when all volunteers stopped its consumption. Finally, we highlight that individuals' metabolic phenotype is reflected in their urine biofluid before and after the dictamnus tea effect while all individuals have some common and different metabolic responses to this tea, implying that each phenotype has a quite different response to this tea consumption.